Qiyas sebagai Metode Tafsir dalam Pemahaman Al – Qur’an - Rahayu, Sri Ulfa; Maulana, Putri Jehan; Utami, Destia Nada (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
As Muslims in everyday life there are decisions that govern our every activity. All of them have specific restrictions and rules to run them. And every legal standard and limitation that regulates Muslims depends on the Al-Qur'an and As-Sunnah. This study is intended to recognize and interpret qiyas as a translation technique in understanding the Qur'an. This study uses a descriptive approach, which involves searching for written sources. The results of this study are the meaning of Qiyas itself and the relationship of Qiyas in the Understanding of the Qur'an where qiyas may actually be carried out with the assumption that there is no Nash that can be used as a halal premise. In this situation where the Al-Qur'an and As-Sunnah do not clearly state the law, it tends to be argued that qiyas is an approach by utilizing ra'yu to study syara' rules. Keywords: Al-Qur'an, Nash, Interpretation, and Nash